Tree organ growth and carbon allocation dynamics impact the magnitude and δ13C signal of stem and soil CO2 fluxes - Tang, Yu; Schiestl-Aalto, Pauliina; Saurer, Matthias; Sahlstedt, Elina; Kulmala, Liisa; Kolari, Pasi; Ryhti, Kira; Salmon, Yann; Jyske, Tuula; Ding, Yiyang; Bäck, Jaana; Rinne-Garmston, Katja T (Oxford University Press (OUP), 2022)
Incomplete knowledge of carbon (C) allocation dynamics in trees hinders accurate modeling and future predictions of tree growth. We studied C allocation dynamics in a mature Pinus sylvestris L. dominated forest with a novel analytical approach, allowing the first comparison of: (i) magnitude and δ13C of shoot, stem and soil CO2 fluxes (Ashoot, Rstem and Rsoil), (ii) concentration and δ13C of compound-specific and/or bulk non-structural carbohydrates (NSCs) in phloem and roots and (iii) growth of stem and fine roots. Results showed a significant effect of phloem NSC concentrations on tracheid growth, and both variables significantly impacted Rstem. Also, concentrations of root NSCs, especially starch, had a significant effect on fine root growth, although no effect of root NSC concentrations or root growth was detected on Rsoil. Time series analysis between δ13C of Ashoot and δ13C of Rstem or δ13C of Rsoil revealed strengthened C allocation to stem or roots under high C demands. Furthermore, we detected a significant correlation between δ13C of Rstem and δ13C of phloem sucrose and glucose, but not for starch or water-soluble carbohydrates. Our results indicate the need to include C allocation dynamics into tree growth models. We recommend using compound-specific concentration and δ13C analysis to reveal C allocation processes that may not be detected by the conventional approach that utilizes bulk organic matter.
Keywords: boreal zone; compound-specific; non-structural carbohydrates; Pinus sylvestris; starch; sucrose; water-soluble carbohydrates